Control Strategies of Steam-injected Gas Turbine in CCHP System. (May 2017) - Zhang, Chi; Wang, Xusheng; Yang, Cheng; Yang, Zeliang
Abstract: In order to relieve energy crisis, more and more distributed energy systems are established and a large number of them use gas turbine as power units. For the in-depth study on the performances of steam injected gas turbine (STIG), the results and discussion show that STIG operation can increase power output and efficiency of generating unit compared with conventional gas turbine. The combined cooling heating and power (CCHP) system with STIG which can adjust the ratio of heat to power elastically and independently, has the ability of accommodating a wider range of electrical loads. The overall off-design characteristics of STIG are obtained using analytical method. For STIG cycle, each operating point is determined by the ratio of steam to air and the turbine inlet temperature calculated by monitoring the turbine outlet temperature. The results present the equal power output curve and equal quantity of heat curve that are meaningful for optimizing operation of CCHP system which works under the off-design conditions.